2018
DOI: 10.1007/s10029-018-1857-2
|View full text |Cite
|
Sign up to set email alerts
|

Is it possible to identify the inguinal nerves during hernioplasty? A systematic review of the literature and meta-analysis of cadaveric and surgical studies

Abstract: Purpose Patients who undergo inguinal hernioplasty may suffer from persistent postoperative pain due to inguinal nerve injuries. The aim of this systematic review and meta-analysis was to provide comprehensive data on the prevalence (identification rates), anatomical characteristics, and ethnic variations of the ilioinguinal (IIN), the iliohypogastric (IHN) and the genital branch of the genitofemoral (GNF) nerves. Methods The systematic literature search was conducted u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…Moreover, the chronic inguinal pain might be caused by the incorporation of the nerve into the mesh due to missed identification of the nerve during surgery. In a systematic review of literature and meta-analysis based on 5265 halfbody examinations, the identification rate of the IIN was 94.4% (95% CI 89.5-97.9) [59]. The subgroup analysis of the studies in which was identified the IIN reported a lower incidence of postoperative pain at 6 months and the same trend in favor of neurectomy.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, the chronic inguinal pain might be caused by the incorporation of the nerve into the mesh due to missed identification of the nerve during surgery. In a systematic review of literature and meta-analysis based on 5265 halfbody examinations, the identification rate of the IIN was 94.4% (95% CI 89.5-97.9) [59]. The subgroup analysis of the studies in which was identified the IIN reported a lower incidence of postoperative pain at 6 months and the same trend in favor of neurectomy.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, the chronic inguinal pain might be caused by the incorporation of the nerve into the mesh due to missed identification of the nerve during surgery. In a systematic review of literature and meta-analysis based on 5265 half-body examinations, the identification rate of the IIN was 94.4% (95% CI 89.5–97.9) [ 59 ]. The subgroup analysis of the studies in which was identified the IIN reported a lower incidence of postoperative pain at 6 months and the same trend in favor of neurectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a systematic review and meta-analysis of worldwide literature reported the identification rates of the inguinal nerves both during open inguinal hernia repair and during cadaveric dissections [ 10 ]. Overall prevalence of IH, II, GF nerves resulted 74.2%, 84.3% e 48.2%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Guidelines recommend intraoperative inguinal nerve identification in order to limit or prevent postoperative pain [6] and to reduce the risk of iatrogenic injury, such as entrapment between prosthetic material and tissue [9]. Recently, a systematic review and meta-analysis of worldwide literature, which analyzed identification rates of the three inguinal nerves, found great heterogeneity among studies in particular in Europe [10]. Inguinal nerve identification is performed routinely by few surgeons, despite several studies concluding that this procedure is safe and does not affect operative time [11][12][13][14].…”
mentioning
confidence: 99%